UJI AKTIVITAS EKSTRAK ETANOL DAUN KERSEN (Muntingia calabura L.) SEBAGAI INHIBITOR ENZIM α-GLUKOSIDASE DENGAN MENGGUNAKAN ELISA READER - Sukmawati Syarif; Nurnaningsih Nurnaningsih; Mamat Pratama (Jurnal Fitofarmaka Indonesia, 2020)
Kersen leaves (Muntingia calabura L) contain metabolites such as alkaloids, anthrax, polyphenols, tannins, saponins and are rich in flavonoid components such as flavones, flavonones, flavan and biflavan which have antidiabetic activity. According to a study conducted by Apriyanti (2016), the ethanol extract of kersen (Muntingia calabura L) at a dose of 250 mg / kg BB significantly reduced blood glucose levels in male wistar rats. In this study aimed at determining IC50 ethanol extract of Muntingia calabura L as an inhibitor of α-glucosidase enzymes using ELISA reader. The method was divided into 3 category is 1 (sample extract), 2 (blank) and 3 (akarbose). Each group added 25 µL α-glucosidase solution (0.25 units / mL then measured using ELISA reader 405 nm. The results showed that the ethanol extract of kersen (Muntingia calabura L) had activity as an inhibitor of α-glucosidase enzyme with IC50 34,197 µg / mL and can be categorized as active.